Comparison of the Analgesic Effects of Dronabinol and Smoked Marijuana in Daily Marijuana Smokers - Cooper, Ziva D (Nature Publishing Group, 2013)
Recent studies have demonstrated the therapeutic potential of cannabinoids to treat pain, yet none have compared the analgesic effectiveness of smoked marijuana to orally administered Δ(9)-tetrahydrocannabinol (THC; dronabinol). This randomized, placebo-controlled, double-dummy, double-blind study compared the magnitude and duration of analgesic effects of smoked marijuana and dronabinol under well-controlled conditions using a validated experimental model of pain. Healthy male (N=15) and female (N=15) daily marijuana smokers participated in this outpatient study comparing the analgesic, subjective, and physiological effects of marijuana (0.00, 1.98, or 3.56% THC) to dronabinol (0, 10, or 20 mg). Pain response was assessed using the cold-pressor test (CPT): participants immersed their left hand in cold water (4 °C), and the time to report pain (pain sensitivity) and withdraw the hand from the water (pain tolerance) were recorded. Subjective pain and drug effect ratings were also measured as well as cardiovascular effects. Compared with placebo, marijuana and dronabinol decreased pain sensitivity (3.56% 20 mg), increased pain tolerance (1.98% 20 mg), and decreased subjective ratings of pain intensity (1.98, 3.56% 20 mg). The magnitude of peak change in pain sensitivity and tolerance did not differ between marijuana and dronabinol, although dronabinol produced analgesia that was of a longer duration. Marijuana (1.98, 3.56%) and dronabinol (20 mg) also increased abuse-related subjective ratings relative to placebo; these ratings were greater with marijuana. These data indicate that under controlled conditions, marijuana and dronabinol decreased pain, with dronabinol producing longer-lasting decreases in pain sensitivity and lower ratings of abuse-related subjective effects than marijuana.